Synthesis of the (1→6)-linked thiodisaccharide of galactofuranose. Inhibitory activity against a β-galactofuranosidase - Repetto, Evangelina (2013)
Methyl (methyl alpha,beta-D-galactofuranosid)uronate was employed as the starting compound,which was per-O-silylated with TBSCl and reduced with LiAlH4 to afford methyl 2,3,5-tri-O-tert-butyldimethylsilyl-b-D-galactofuranoside (2b) as akey precursor for the preparation of methyl per-O-tert-butyldimethylsilyl-6-thio-b-D-galactofuranos ide (12). The free thiol group of 12 was glycosylated and the product O-deprotected to afford the target b-D-Galf-S-(1,6)-b-D-Galf-OMe (14). The conformations of this thiodisaccharide were preliminarily studied using combined theoretical calculatio ns and NMR data.Further-more, the glycomimetic 14 showed to be a competitiv einhibitor of the beta-galactofuranosidase from Penicillum fellutanum (Ki = 3.62 mM).